How Does Driver Turnover Affect Motor Carrier Safety Performance and What Can Managers Do About It?. Issue 3 (28th June 2017) - Miller, Jason W.; Saldanha, John P.; Rungtusanatham, Manus; Knemeyer, Michael
Abstract : The trucking industry is the lifeblood of supply chains. Truck driver turnover and motor carrier safety are two salient issues affecting this industry. While turnover by itself presents a challenge due to the cost of replacing drivers, it takes on additional urgency because turnover may affect motor carrier safety. However, driver turnover research has focused predominantly on identifying factors affecting turnover, thus resulting in limited understanding of how turnover affects motor carrier performance, particularly with regard to safety. This reduces our ability to provide guidance to managers who have to address driver turnover. In this article, we extend prior research by drawing from several theoretical lenses to develop and test theory of the turnover–safety relationship. Furthermore, we investigate whether carrier managers can mitigate the effect of turnover on safety by embedding knowledge in carriers' routines using activity control, a formal management control mechanism. We employ a longitudinal data set composed of primary and secondary data sources to test our hypotheses. We find the turnover–safety relationship is best characterized by a monotonic negative attenuated pattern and that high levels of activity control mitigate the negative effect of driver turnover on motor carrier safety in domains more under drivers' control.